EVOLUTION OF OUTSOURCING RELATIONS IN THE OIL & GAS INDUSTRY OF RUSSIA - D. A. Stapran (Модернизация, инновация, развитие, 2018)
Purpose: the purpose of this article is to study the evolution of oil&gas service outsourcing, to determine trends and factors that define these trends. The article also tests the methodology of “five forces of outsourcing” model formulated by the author.Methods: a number of factors, which constitute the “five forces of outsourcing” model, proposed by the author, influences outsourcing. The elements of the model are transaction costs, competitive advantages, trust and commitment, level of economic development and the “sourcing cycle”. The article uses extensive amount of company data and market research, contains assessment of the market volume and prospects of its growth.Results: oil & gas services are the most dynamic type of outsourcing in the oil & gas industry. The article analyses the evolution of oil & gas services outsourcing for the past 20 years through the lenses of the “five forces” methodology. This type of outsourcing first emerged when the Russian economy turned to market economy. It started from the “ground zero” point, evolved, matured and finally became an indispensable part of the oil & gas industry nowadays. At the same time the oil&gas industry reimagined its value chain, having concentrated on its competitive advantages and transferred service business processes to outsourcing providers. The market of oil & gas services outsourcing passed the test when an attempt to create a state monopoly in this field failed due to the maturity of the market.Conclusions and relevance: the task of increasing eficiency of the oil & gas industry in Russia is paramount especially taking into account the decrease in oil prices. Outsourcing is, undoubtedly, one of the means of achieving such eficiency. Its volumes will keep growing. Yet some companies will continue to test the effectiveness of insourcing operations. The analysis also confirmes the validity of the “five forces” methodology as well as the “sourcing cycle” theory.